Blood parameters and reproductive hormone profile of female Choloepus hoffmanni in captivity - Herra-Vargas, Sofía (2018)
In wild animal species, the use of non-invasive and non-stressful procedures to determine hormone profiles, such as fecal steroid measurements, has considerably increased the comprehension of their reproductive physiology. Since there is limited information related to the reproductive hormone profiles of the two-toed sloth, Choloepus hoffmani, a study was conducted in captive specimens at the “Sloth Sanctuary” (Cahuita, Limón, Costa Rica), in order to determine: (i) the reliability of the fecal progesterone and estrogen extraction and its quantification with an AIA-360® analyzer, (ii) assess blood parameters in this species and (iii) evaluate if there is a correlation between fecal and plasmatic steroids. The study was performed over a three-month period, from November, 2013 to January, 2014, with a total amount of 208 fecal samples collected from five sexually mature females weighing 6.32 Kg in average. The average of the median concentrations of progesterone in feces of the five females was 124.21 ng/g, and 1 708.95 pg/g for estrogen. The average minimal and maximal values were 50.96 ng/g and 1 057.46 ng/g for progesterone and, 1 191.77 pg/g and 2 159.24 pg/g for estradiol. In plasma, progesterone median values were 1.26 ng/mL, showing a minimum of 0.32 ng/mL and 12.84 ng/mL as maximum values. The plasmatic estrogen levels were below the detection limit of the equipment (25 pg/mL). Although there was no strong statistical correlation between the fecal and plasmatic progesterone fluctuations, our data suggests that the plasmatic events are mostly reflected in feces two days afterwards. Also, the levels of progesterone were elevated during the first half of November and, subsequently, showed a successive and important reduction in all the females tested. Finally, our results demonstrated that fecal steroid extractions and their measurement in a AIA-360®, allowed the successful detection and represents an alternative non-invasive determination of hormone profiles in C. hoffmani.